2018
DOI: 10.2478/mjss-2018-0153
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Practices and Infant Mortality in Cross River State, Nigeria: A Sociological Perspective

Abstract: One of the greatest challenges confronting the government in Nigeria today is the need to reduce infant and child morbidity and mortality in order to achieve the sustainable development goal 2030. Infant mortality is generally used to describe the death of infants or babies that were born alive but died before their first birthday. There is generally marked inequality in infant death between developed and developing nations but also within them. Culture has been found to influence the health of the people espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…A number of traditional food taboos adopted by pregnant women are carried over to their children after delivery. These practices include not giving children certain foods [ 40 ]. Food taboos also have a strong effect on infant feeding and undermine optimal infant feeding practices [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of traditional food taboos adopted by pregnant women are carried over to their children after delivery. These practices include not giving children certain foods [ 40 ]. Food taboos also have a strong effect on infant feeding and undermine optimal infant feeding practices [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Food taboos also have a strong effect on infant feeding and undermine optimal infant feeding practices [ 41 ]. The belief of restricting children from eating protein-rich foods such as meat and eggs, because it will cause children to steal as meat and eggs are normally stolen by dogs, deprive children of these nutritious foods, which may lead to malnutrition [ 40 ]. The World Health Organization [ 42 ] reported that 45% of global deaths among children under 5 years of age are attributed to under-nutrition, which is approximately three million deaths each year.…”
Section: Introductionmentioning
confidence: 99%
“…En estas sociedades, en las que existe una fuerte creencia en la brujería y el destino, a la enfermedad se le suelen atribuir tres causas: natural, sobrenatural y mística. Siempre que un niño está gravemente enfermo se busca la interpretación de la enfermedad (Undelikwo, 2018).…”
Section: El Concepto De Enfermedadunclassified
“…A number of traditional food taboos adopted by pregnant women are carried over to their children after delivery. These practices include not giving children certain foods [35]. Food taboos also have a strong effect on infant feeding and undermine optimal infant feeding practices [36].…”
Section: Introductionmentioning
confidence: 99%
“…Food taboos also have a strong effect on infant feeding and undermine optimal infant feeding practices [36]. The belief of restricting children from eating protein rich foods such as meat and eggs, because they will steal, deprive children of these nutritious foods, which may lead to malnutrition [35]. World Health Organization [37] reported that 45% of global deaths among children under ve years of age are attributed to under-nutrition, which is approximately three million deaths each year.…”
Section: Introductionmentioning
confidence: 99%